Execução extrajudicial - Neves, Fernando Crespo Queiroz (2016)
This thesis for a doctorate is inserted in the search line of effectiveness of Private Law and Civil Liberties, in research nucleus in Civil Procedural Law. The work discusses the historical introduction of constant means laid down in the search for effectiveness in the solution of disputes through alternative procedures without leaving aside the maximum guarantee of full access to the Judiciary. In the quest for rationalization of civil procedure, having been identified as the extrajudicial execution process , especially for collection of the debt of the Union, the States, Federal District and municipalities, it is one of the main bottlenecks in the length of civil proceedings, we treat, at this work, the possibility of non-judicial procedure for the collection of the credit embodied in extrajudicial titles and its compatibility with existing principles